أثر خصائص القوى العاملة ومالكي المزارع على الإنتاجية الزراعية الأردنية دراسة حالة - وادي الأردن - محمد الحبيس, محمود عبد الله (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تناولت هذه الدراسة أثر خصائص القوى العاملة على الإنتاجية الزراعية في منطقة وادي الأردن. حيث اعتمدت الدراسة على عينة عشوائية, تتكون من (323 ) مزارعاً, واستخدمت الأساليب الإحصائية الوصفية والتحليلية لأغراض الدراسة. توصلت الدراسة إلى نتائج هامة ، أبرزها أن غالبية المالكين للأرض, هم مزارعون, ويتميزون بمستوى تعليمي منخفض، وتزيد أعمارهم عن 46 سنة ، وتجمع الوسائل الزراعية المستخدمة ما بين التقليدي والحديث، وأن العمال العاملين هم من الذكور, وبمستوى تعليمي منخفض، والغالبية العظمى من العمال الدائمين والمؤقتين هم من جنسيات غير أردنية. This study deals with the impact of the characteristics of labour force and land owners upon the agricultural productivity in the Jordan valley. A random sample of 323 agriculturist in the Jordan valley was selected. The study revealed important results. The majority of land owners were themselves the agriculturists, with a low educational level and an average age above 46 years. Most labors are males with a low educational level, and the majority of the permanent and temporary labors were foreigners. The agricultural productivity varies according to the above mentioned differentiating characteristics utilized. The author recommends enhancing the educational level of labourers to ensure improving agricultural productivity.